PENGARUH DEBT EQUITY RATIO, KOMITE AUDIT DAN LABA OPERASI TERHADAP AUDIT DELAY PADA BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Rukmini, Meme; Pramana, Andy Chandra; Prasaja, Mukti (Universitas Nusantara PGRI Kediri, 2021)
This pandemic period is a difficult time for real sector entrepreneurs, the impact of the pandemic makes real sector entrepreneurs think extra so that their income does not drop dramatically. Investing in the stock exchange becomes one of the alternatives that many entrepreneurs take. By investing or buying in the stock market, they only need the ability to analyze the audited financial statements that have been provided on the Indonesia Stock Exchange (IDX). IDX facilitates investors by adjusting the financial statements of auditing companies. But there is an issue that is often encountered when issuers are late in reporting their audited financial statements due to audit delays. This has an impact on the delay in the information needed by investors. We need to know that many factors influence the occurrence of audit delays. This research aims to find out the influence of debt equity ratio, audit committee and operating profit on audit delays on Badan Usaha Milik Negara (BUMN) which is listed on the IDX. Using multiple regression analysis, the results of this study state that simultanly the DER, audit committee and operating profit have an influence on audit delays. While partially, the audit committee and operating profit has a significance value below 0.05 so that it shows an influence on audit delays. However the significance value of the DER is above 0.05 so the DER has no effect on the audit delay.